mTORC2 protects the heart from high-fat diet-induced cardiomyopathy through mitochondrial fission in Drosophila - Liu, Peiduo; Chang, Kai; Requejo, Guillermo; Bai, Hua (Frontiers in Cell and Developmental Biology, 2022)
High-fat diet (HFD)-induced obesity has become the major risk factor for the development of cardiovascular diseases, but the underlying mechanisms remain poorly understood. Here, we use Drosophila as a model to study the role of mTORC2 in HFD-induced mitochondrial fission and cardiac dysfunction. We find that knockdown of mTORC2 subunit rictor blocks HFD-induced mitochondrial fragmentation and Drp1 recruitment. Knockdown of rictor further impairs cardiac contractile function under HFD treatment. Surprisingly, knockdown of Akt, the major effector of mTORC2, did not affect HFD-induced mitochondrial fission. Similar to mTORC2 inhibition, knockdown of Drp1 blocks HFD-induced mitochondrial fragmentation and induces contractile defects. Furthermore, overexpression of Drp1 restored HFD-induced mitochondrial fragmentation in rictor knockdown flies. Thus, we uncover a novel function of mTORC2 in protecting the heart from HFD treatment through Drp1-dependent mitochondrial fission.